Assessment of the Difficulties and Care Burdens of Caregivers of Children with Complex Health Care Needs at Home: Descriptive Study. - YETİMOĞLU, Merve; BULUT, Hacer KOBYA (Turkiye Klinikleri Journal of Nursing Sciences, 2024)
Objective: The research was conducted to determine the difficulties experienced by caregivers of children with complex health care needs at home and to evaluate their care burden. Material and Methods: The primary caregivers of 55 children who were registered in the home healthcare services unit of a province in the northeast of Türkiye and who met the inclusion criteria for the study were included. In the study, data were collected by face-to-face interview method by making home visits with the information form and Caregiver Burden Scale. Standard deviation, mean value, frequency, and percentage were used in the analysis of descriptive data. Mann-Whitney U test and Kruskal-Wallis test were used to analyse categorical data. Results: The mean age of the children in the study was 11.2±5.99 years. The majority of primary caregivers stated that they had difficulties in the care of the child, respectively, in the aspiration procedure (66.6%), the use of home-type mechanical ventilators (66.6%) and tracheostomy care (61.9%). It was found that caregivers who stated that their psychological health and social relations were impacted had a higher caregiver burden and there was a significant difference (p<0.05). Conclusion: In the study, primary caregivers have difficulties in caring for children with complex health care needs at home and their average care burden is high.